Pelaksanaan Kegiatan “Cinta Lingkungan” dalam Membentuk Karakter Peduli Lingkungan di SMP Negeri 4 Gunung Talang - Islami, Yulvi; Wiza, Rahmi (TSAQOFAH, 2025)
This study aims to describe the implementation of the "Cinta Lingkungan" (Love for the Environment) program at SMP Negeri 4 Gunung Talang as an effort to cultivate environmental awareness among students. A qualitative approach with a case study method was employed. Data sources included the principal, program supervisors, and both participating and non-participating students, supported by relevant documentation. The findings indicate that the implementation of the "Cinta Lingkungan" program involved the development of a regular schedule, various environmental activities such as school area cleaning and tree planting, and the utilization of the surrounding school environment as the activity site. Program evaluation was based on timing and types of activities conducted. However, supervisors faced several challenges, including students’ initial lack of awareness regarding the importance of environmental preservation and limited operational funding. These findings suggest that the "Cinta Lingkungan" extracurricular program can serve as a strategic means to instill environmental care values but requires sustained support from both the school and students to achieve optimal outcomes.